Clinical guideline for mandibular teeth local anesthesia in operative dentistry (Эндодонтия Today)
The authors presented the highest standards of mandibular teeth anesthesia used in dentistry. Different variants of anesthesia, depending on the group membership of the tooth, the expected duration of the intervention and nosology are presented. The algorithm of anesthesia for mandibular block failure is proposed. Described the indications for the use of periodontal ligament and intraseptal anesthesia methods. Recommendations to the choice of the injection needle and dosage of the anesthetic are given.